Acute Scrotal Pain: A Two Year Prospective Cohort Study (Medical Forum Monthly, 2024)
Objective: To determine the cause of acute scrotal pain and its subsequent treatment.Study Design: Prospective cohort studyPlace and Duration of Study: This was carried out in Armed Forces Institute of Urology Rawalpindi and Combined Military Hospital Abbotabad from 1st Jan 2014 to 31st Dec 2015Materials and Methods: A total of 116 patients who presented with acute scrotal pain were included in the study. Those presenting within six hrs and a history consistent with testicular torsion underwent urgent exploration. Those presenting with a history of more than six hours or within six hrs but clinically suggestive of testicular torsion underwent emergency Doppler ultrasonography before surgery.Results: The occurance of different conditions were as follows: testicular torsion 10, torsion of appendix testis 02, Epididymo-orchitis 4, orchitis 10, trauma 12, infected hydrocele 12 ,strangulated inguinal hernia 3, and idiopathic scrotal pain 18. Mean age(in years) for testicular torsion was 13±5 for Torsion of appendix testis 16±8,and for epididymo-orchitis 50±22. Mean duration of symptoms(in hours) for testicular torsion was 10±4, torsion of appendix testis was 11±3 and epididymo-orchitis 18±14. During surgery for testicular torsion ,detorsion of the affected testis was done and bilateral orchidopexy was performed in 04 patients. Orchidectomy with orchidopexy of the contralateral side was done in 06 patients who had nonviable testis.Conclusion: Acute scrotal pain is a common presentation. Our study concluded that in such cases colour doppler ultrasonography is important to reach a definitive diagnosis. The occurance of testicular torsion is very high in patients less than 18 years of age .Moreover if there is a clinically strong suspicion of testicular torsion then yield of immediate surgery is high, because delay in exploration proves detrimental to the efforts of salvaging the testis. Patients with epididymo-orchitis respond well to ciprofloxacin prescribed for two weeks.